Framework for Evaluating the Impact of Advanced Practice Nursing Roles. Issue 2 (11th February 2016) - Bryant‐Lukosius, Denise; Spichiger, Elisabeth; Martin, Jacqueline; Stoll, Hansruedi; Kellerhals, Sabine Degen; Fliedner, Monica; Grossmann, Florian; Henry, Morag; Herrmann, Luzia; Koller, Antje; Schwendimann, René; Ulrich, Anja; et al.
Abstract: Purpose: To address the gap in evidence‐based information required to support the development of advanced practice nursing (APN) roles in Switzerland, stakeholders identified the need for guidance to generate strategic evaluation data. This article describes an evaluation framework developed to inform decisions about the effective utilization of APN roles across the country. Approach: A participatory approach was used by an international group of stakeholders. Published literature and an evidenced‐based framework for introducing APN roles were analyzed and applied to define the purpose, target audiences, and essential elements of the evaluation framework. Through subsequent meetings and review by an expert panel, the framework was developed and refined. Findings: A framework to evaluate different types of APN roles as they evolve to meet dynamic population health, practice setting, and health system needs was created. It includes a matrix of key concepts to guide evaluations across three stages of APN role development: introduction, implementation, and long‐term sustainability. For each stage, evaluation objectives and questions examining APN role structures, processes, and outcomes from different perspectives (e.g., patients, providers, managers, policy‐makers) were identified. Conclusions: A practical, robust framework based on well‐established evaluation concepts and current understanding of APN roles can be used to conduct systematic evaluations. Clinical Relevance: The evaluation framework is sufficiently generic to allow application in developed countries globally, both for evaluation as well as research purposes.